TINJAUAN KEPATUHAN PAJAK ATAS PENERAPAN E-BILLING DAN E-FILING WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA TEMANGGUNG - Kurniawati, Dinda Safitri; Nurhanifah, Afifa (Universitas Trilogi, 2023)
This study aims to review the implementation of e-billing and e-filing, the level of compliance of Individual Taxpayers and SMEs, and the effect of the COVID-19 pandemic on the use of e-billing and e-filing. This research was conducted at KPP Pratama Temanggung for Individual Taxpayers periods 2018 - 2020. The results of the study can be concluded that KPP Pratama Temanggung has implemented the use of e-billing and e-filing, and the level of compliance seen from the period of submitting Annual Tax Returns in 2020 the number of Taxpayers who filed Tax Returns on time has decreased. The effect of the COVID-19 pandemic on tax payments in 2020 on the amount of tax revenue from MSME taxpayers has decreased. Meanwhile, the effect of the COVID-19 pandemic on the reporting of Annual Tax Returns does not affect e-filing reporting when viewed from the increase in the realization of the submission of Annual Tax Return reporting. However, when viewed from the level of compliance of the Annual Tax Return reporting period with e-filing, Taxpayers who submit Annual Tax Returns with e-filing on time have decreased.Keywords: E-billing, E-Filling, Tax Compliance